Higgs Mode of Planar Coupled Spin Ladders and its Observation in C₉H₁₈N₂CuBr₄ - Ying, T.; Schmidt, Kai Phillip; Wessel, S. (Physical Review Letters, 2019)
Polarized inelastic neutron scattering experiments recently identified the amplitude (Higgs) mode in C9H18N2CuBr4, a two-dimensional near-quantum-critical spin-1/2 two-leg ladder compound, which exhibits a weak easy-axis exchange anisotropy. Here, we theoretically examine the dynamic spin structure factor of such planar coupled spin-ladder systems using large-scale quantum Monte Carlo simulations. This allows us to provide a quantitative account of the experimental neutron scattering data within a consistent quantum spin model. Moreover, we trace the details of the continuous evolution of the amplitude mode from a two-particle bound state of coupled ladders in the classical Ising limit all the way to the quantum spin-1/2 Heisenberg limit with fully restored SU(2) symmetry, where it gets overdamped by the two-magnon continuum in neutron scattering.
CRIS-Team Scopus Importer:2019-05-02